الجماليات الفنية في رواية "حوبة ورحلة البحث عن المهدي المنتظر" لعز الدين جلاوجي - بركة, ناصر; برباش, نوال (جامعة الوادي - university of Eloued, 2020)
شهدت الرواية العربية عامة والجزائرية خاصة عبر تاريخها الطويل العديد من التجارب الإبداعية على المستويين الشكلي والمضموني، محاولة إعادة صياغة المعمار الروائي بما يتناسب مع الواقع والفكر العربي، الأمر الذي جعل النقاد يطلقون على هذا العصر "عصر الرواية"، ومن الروائيين الجزائريين الذين طوروا وأدخلوا تقنيات جديدة في الرواية يمكن ذكر: "الطاهر وطار، أحلام مستغانمي، واسيني الأعرج، عبد الحميد بن هدوقة...الخ"، ولقد تعددت دواعي الميل إلى التقنيات الحداثية في الرواية والدعوة إلى التحرر من سيكونية النص التقليدي حيث تهدف الكتابة الروائية الجديدة إلى استثمار العديد من البنيات الفنية الجمالية من أجل تحقيق المغايرة وذلك من مثل إثارة الأسئلة بالمتن والأبنية والأنساق لغة وخطابا، والتركيز على جمالية السرد والحوار والتنقل بين المركبات القصيصة، وتوظيف الفنون الإبداعية الأخرى كالسينما والفن التشكيلي والسيرة الذاتية فضلا عن كيفية عرض الشخوص الروائية، الكلمات المفتاحية: الرواية، الخيال،اللغة، الشخصيات، الزمان، المكان Abstract The Arabophone novel in general and Algerian novel in specific, has witnessed through its long history many creative experiences on both the levels: formal and the substantive. It attempted to reenact the novelist architecture according to Arab reality and thought; the thing that led critics to call this era "the age of the novel". "Tahir Watar, Ahlam Mostaganemi, Oasini al-A'araj, and Abdel Hamid Ben Hudouka, are among the Algerian novelists who developed and introduced new techniques in the novel. There are many reasons for the tendency to include modernist techniques in the novel and the call for its liberation from the traditional textualism. Many aesthetic structures have been created in order to achieve differentiates, such as raising questions in terms of structure, structures and formats, language and speech, focusing on the aesthetics of narration, dialogue and mobility among short vehicles, and the use of other creative arts such as cinema, art and biography as well as the presentation of narrative characters. Keywords: fiction-langage-character-time-space.
The artistic aesthetics in the novel "houba and a trip search about the expected mahdi" of Azzeddine Djlaoudji
مقال
Keywords: الرواية، الخيال،اللغة، الشخصيات، الزمان، المكان; fiction-langage-character-time-space